Resistive Index Value of Superior Mesenteric Artery In Preterm Infants With Necrotizing Enterocolitis - Harry Galuh Nugraha*, Edwam Akbar, Atta Kuntara (Innovative Journal of Medical and Health Sciences, 2020)
Aims: to find out the comparison of RI values of superior mesenteric artery in premature infants with NEC and without NEC. Material and methods: This study was an observational analytic study, with a case-control study design, where the sampling method was using consecutive sampling in the NICU Room, Anturium and Radiology Department Dr. Hasan Sadikin General Hospital Bandung from September to October 2019. Data processing uses unpaired T-test. Results: The total sample was 22 subjects, consisting of 11 with positive NEC and 11 negative NEC, with an average gestational age of 31.36 weeks and an average birth weight of 1490.45 grams. In the positive NEC group, the average RI value was 0.90 and in the negative NEC group, the average RI value was 0.70. Statistical test results with unpaired T-test showed that there was a statistically significant increase in the value of superior mesenteric artery RI in premature infants with NEC compared to premature infants without NEC with a p-value = 0.0001 (p-value < 0.05). Conclusion: There was an increase in the value of superior mesenteric artery RI in premature infants with NEC compared to premature infants without NEC with a value of p = 0.0001 (p-value <0.05). Key words: Necrotizing Enterocolitis–Superior Mesenteric Artery–Ultrasonography